HOW TO BECOME A PRODUCTIVE FAN? THE EXISTENCE OF FAN TALKS AS FANDOM PRODUCTIVITY - Rina Sari Kusuma; Siti Aminah Munasah (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Fans draw sharply the line between what falls within their fandom and what does not. Accumulation and appreciation of knowledge regarding fan’s objects of fandom are important for fan cultural capital. Fiske’s pre-internet model of fan productivity occurs at the interface between industrially-produced cultural commodities and the everyday life of the fan. Fan talk is a circulation mechanism of certain meanings of the object of fandom implying the membership of a particular fan community. BTS is a K-Pop group that uses online exposure with a variety of contents ranging from members personal message to behind-the-scenes footage to create deeper levels of intimacy with their fans. This helps them to advance their careers and create alliances with their fans. This study uses a descriptive qualitative approach to explore BTS fan’s participation in fan talk activities shared within face-to-face communication. The data collection techniques used were in-depth interviews and participant observations of four BTS’s fans (called ARMY). The result shows that fan talk is one way of expressing the existence of fans. Digital media and the internet have allowed BTS' fans to share a wide range of signifiers and meanings from their music quickly and easily. This has created a form of symbolic interaction among fans that can be used to communicate concepts and ideas among one another. This enunciative productivity of fans is also serving a widespread promotional function for non-fans.